2015
DOI: 10.1016/j.jphotobiol.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic antimicrobial chemotherapy: First steps towards a sound approach for microbe inactivation

Abstract: Sonodynamic therapy (SDT) relies on the ability of ultrasound to activate sonosensitisers and trigger the generation of reactive oxygen species (ROS) to achieve cell death. SDT was explored as an anticancer approach until 6 years ago, when its potential application as an antimicrobial strategy was pointed out and the term "sonoantimicrobial chemotherapy" (SACT) was coined. The excellent penetration of ultrasound in liquid media make SACT particularly promising approach for the noninvasive treatment of deep-sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 55 publications
(53 reference statements)
0
53
0
1
Order By: Relevance
“…To overcome the problems associated with antifungal resistance, studies have been performed to search for alternative therapies to treat infections. aPDT (Dovigo, Pavarina, Carmello et al 2011;Dovigo et al 2013;Pereira et al 2011;Costa et al 2012) and SDT (Ma et al 2009;Wang et al 2014;Zhuang et al 2014;Costley et al 2015;Serpe and Giuntini 2015) have been suggested as promising therapies for the inactivation of microorganisms. According to the data, it was observed that the application of aPDT, mediated by PDZ at 100 mg l −1 or RB 10 μM, eradicated planktonic cultures of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the problems associated with antifungal resistance, studies have been performed to search for alternative therapies to treat infections. aPDT (Dovigo, Pavarina, Carmello et al 2011;Dovigo et al 2013;Pereira et al 2011;Costa et al 2012) and SDT (Ma et al 2009;Wang et al 2014;Zhuang et al 2014;Costley et al 2015;Serpe and Giuntini 2015) have been suggested as promising therapies for the inactivation of microorganisms. According to the data, it was observed that the application of aPDT, mediated by PDZ at 100 mg l −1 or RB 10 μM, eradicated planktonic cultures of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that certain PS can also be activated by ultrasound (US), and as a result, the PS may also be referred to as a sonosensitizer (SS). This approach is known as sonodynamic therapy (SDT) (Ma et al 2009;Serpe and Giuntini 2015). The advantage of SDT when compared to aPDT is that US propagates deeper into the tissue than light; therefore, SDT may be used to treat deeper lesions overcoming the limitations of light propagation and delivery presented by aPDT (Ma et al 2009;Costley et al 2015;Serpe and Giuntini 2015).…”
Section: Strain and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with light activation, ultrasound can be selectively focused on a specific area, thus activating only PS molecules located in the affected area. Ultrasound can also easily penetrate into tissues, which opens prospects for its application in treatment of internal lesions and infections, without the need for invasive devices [33,34]. Ultrasonic irradiation of PSs initiates the formation of highly active cytotoxic species-ROS and free radicals-which lead to the death of pathogenic cells.…”
Section: Sonodynamic Excitation Of Photosensitizersmentioning
confidence: 99%
“…Sonodynamic therapy is also offered as treatment for atherosclerosis [44]. The applicability of sonodynamic antimicrobial chemotherapy (SACT) for the treatment of infectious diseases has been confirmed by various research groups [33,34]. We have previously demonstrated the effectiveness of RB activated by ultrasonication for eradication of Gram-positive S. aureus and Gram-negative E. coli [29, 45,46].…”
Section: Sonodynamic Excitation Of Photosensitizersmentioning
confidence: 99%